Comprehensive analysis of cellular senescence-related genes in the prognosis, tumor microenvironment, and immunotherapy/chemotherapy of clear cell renal cell carcinoma - Lu, Caibao; Wang, Yiqin; Nie, Ling; Chen, Liping; Li, Moqi; Qing, Huimin; Li, Sisi; Wu, Shuang; Wang, Zhe (Frontiers in Immunology, 2022)
Background: The transcriptome public database and advances in biological discoveries contributed to significant progresses in identifying the drivers of cancer progression. Cellular senescence (CS) is considered as a leading factor resulting in cancer development. The purpose of this study was to explore the significance of CS-related genes in the molecular classification and survival outcome of clear cell renal cell carcinoma (ccRCC). Methods: CS-related genes were obtained from CellAge database, and patients from TCGA-KIRC dataset and ICGC dataset were clustered by ConsesusClusterPlus. The characteristics of overall survival (OS), genomic variation, and tumor microenvironment (TME) of each cluster were analyzed. Least absolute shrinkage and selection operator (LASSO) Cox regression analysis was conducted to develop a CS-related risk model to score ccRCC patients and assess the risk scores in predicting patients’ response to immunotherapy and chemotherapy. A nomogram based on risk model was established to improve the risk stratification of patients. Results: CcRCC was divided into three molecular subtypes based on CS-related genes. The three molecular phenotypes showed different OS and clinical manifestations, mutation patterns and TME states. Five genes were obtained from 9 differentially expressed CS-related genes in the three molecular subtypes to develop a risk model. Patients with ccRCC was divided into high- and low-risk subgroup. The former showed an unfavorable OS, with significantly higher genomic variation rate, TME score and numerous immune checkpoint expression when compared to low-risk subgroup. Risk score reflected the response of patients to axitinib, bortezomib, sorafenib and sunitinib and temsirolimus. Conclusions: In general, CS-related genes divided ccRCC into three molecular subtypes with distinct OS, mutation patterns and TME states. The risk model based on the five CS-related genes can predict the prognosis and therapeutic outcome of ccRCC patients, providing a theoretical basis for further study on the molecular mechanism of CS-related ccRCC.